Imaging DOAS detection of primary formaldehyde and sulfur dioxide emissions from petrochemical flares. Issue 15 (15th August 2013) - Pikelnaya, Olga; Flynn, James H.; Tsai, Catalina; Stutz, Jochen
Abstract: [1] Metropolitan areas with a high number of petrochemical facilities are often struggling to meet current and future air quality standards. The Houston‐Galveston area, for example, continues to be in noncompliance with the U.S. federal air quality standard of ozone, despite significant progress in mitigating air pollution. In recent years, the magnitude and role of primary emissions of ozone‐forming chemicals, and in particular formaldehyde, from flares in petrochemical facilities have been discussed as a potential factor contributing to ozone formation. However, no direct observations of flare emissions of formaldehyde have thus far been reported. Here we present observations of formaldehyde and sulfur dioxide emissions from petrochemical flares in the Houston‐Galveston area during the 2009 Formaldehyde and Olefin from Large Industrial Sources campaign using a new imaging differential optical absorption spectrometer (I‐DOAS). Formaldehyde emissions from burning flares were observed directly above the flare stack and ranged from 0.2 to 8.5 kg/h. Unlit flares were found not to emit formaldehyde. SO2 emission rates from a burning acid gas flare ranged between 2 and 4 kg/h. None of the sampled flares coemitted HCHO and SO2 . Comparison of the emission fluxes measured by the I‐DOAS instrument with those from emission inventories and with fluxes calculated from plumes detected by the long‐path DOAS over downtown Houston shows that the flares observed by the I‐DOAS were relatively small. While burning flares clearly emit HCHO, a larger observational database is needed to assess the importance of flare emissions for ozone formation. Key Points: Burning petrochemical flares emit formaldehyde at rates of 0.3‐2.5 kg/hr Co‐emission of formaldehyde and sulphur dioxide from flares was not observed Small flares were observed, larger flares are expected to emit more HCHO